Kontribusi Pendidikan Nilai Tanggung Jawab Dan Kematangan Emosi Dalam Membentuk Konsistensi Perilaku Disiplin Siswa - Salsabiila Roudlotul Firdaus; Ommar Sharief; Tarjono; Muhammad Alfi Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
The inconsistency of student disciplinary behavior remains a major challenge in various educational institutions, often addressed solely through punitive approaches without holistically touching psychological aspects. This study aims to examine the contribution of responsibility value education (cognitive-moral domain) and emotional maturity (affective domain), both partially and simultaneously, in forming the consistency of student disciplinary behavior. This study employed a quantitative approach with an ex-post facto correlational design. The sample consisted of 34 eleventh-grade students at MA Al-Irsyad Tengaran 2 Majalengka, selected using the total sampling technique. Data were collected using Likert-scale questionnaires that had met strict validity and high reliability tests (Cronbach's Alpha > 0.80). The data were analyzed using multiple linear regression. The results demonstrated that responsibility value education and emotional maturity simultaneously provided a positive and highly significant contribution to the consistency of student disciplinary behavior with an explanatory power of 72.0%. Partially, emotional maturity was found to be a more dominant predictor in influencing discipline compared to the moral cognition of responsibility. It is concluded that persistent rule compliance cannot be formed in isolation; rather, it requires an absolute synergy between ethical awareness and affective resilience. This study recommends a paradigm shift in school disciplinary systems from behavioristic-punitive measures to an integrative character education curriculum